Validity of Electronic Student Worksheets to Improve Students' Metacognitive Skills Through PBL on Petroleum Materials - Iga Putri Subandi; Rusly Hidayah (Universitas Pendidikan Mandalika, 2023)
This study aims to develop Electronic LKPD to improve students' metacognitive skills through problem-based learning model on petroleum material with validity criteria. The procedure used in the research is 4D by Thiagarajan and in the limited test a onegroup pretest-posttest research design was carried out. The development of teaching materials in the study refers to Thiangarajan's 4D model (1974) which consists of 4 stages, namely Define, Design, Develop, and Disseminate, but because in this development research using limited product trials, the research stages are carried out in sequence until the Develop stage (Thiagarajan, Sammel, & Sommel, 1974). This trial design used a one group pretest-posttest design. In this design, two tests were carried out, namely before being given treatment called pretest and after treatment called posttest.The instrument used is a media validation sheet for the validity of Electronic LKPD. In one of the public high schools in Mojokerto, metacognitive skills are very low at 20%. Based on interviews with chemistry teachers, it was found that the chemistry learning model in class often applies lecture models, discussions, so that students are less actively involved in learning and teachers have never tested students' metacognitive skills. This has an impact on the metacognitive skills of students in chemistry lessons are less than satisfactory, especially in petroleum material. The results of product validation consist of the mode on the content criteria getting validity 4 and the mode on the construct criteria getting validity 4 with both criteria being very valid. So that the Electronic LKPD developed is valid to improve students' metacognitive skills through the Problem Based Learning (PBL) model on Petroleum Material.